Pengaruh Pengetahuan, Sikap, dan Religiusitas Terhadap Minat Beli Produk Fashion Kulit Halal - Wandi Suwarno; Anita Priantina (JURNAL ADMINISTRASI BISNIS (JAB), 2024)
Fashion leather includes garments made from animal skins and is used extensively in the manufacture of various items, including jackets, shoes, bags, and accessories. This popularity is due to the high aesthetic value and durability of leather fashion products. This study aims to investigate the influence of knowledge, attitude, and religiosity on the purchase intention of leather fashion products. Using a quantitative approach, data was primarily collected through questionnaires distributed among the residents of Bogor. The analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS 3.0. The results show that knowledge, attitude, and religiosity have a significant influence on the purchase intention of leather fashion products in the city of Bogor. What sets this study apart from others is its unique approach to understanding consumer behavior in choosing leather fashion products in Bogor. While previous studies have mainly focused on variables such as price and product quality, this study introduces the variables of knowledge, attitude, and religiosity to measure the level of purchase interest.